Job Mobility and Segmentation in Australian City Labour Markets - Welters, R; Bill, A; Mitchell, W (My University, 2006)
Gordon (2005: 2) hypothesises that in 15 years, cities have developed a unique potential for achieving successful economic outcomes, owing to their ‘density, diversity and openness to change’. Accordingly, by virtue of their scale, networks and advanced service functions cities provide greater potential for interaction and readier access to innovation; they also afford workers higher earnings and greater opportunity to appropriate productivity gains through job mobility. However, the benefits of job mobility arguably accrue only to those individuals located in dynamic local labour markets and in growing occupations with ‘deep’ skillsets. The flip-side of flexibility is more insecurity, associated with casualisation and intense job-competition for low-skilled positions. When labour markets are job rationed overall, more able workers successfully compete for low-skill jobs at the expense of the least skilled workers (see Bill and Mitchell, 2006).
Centre of Full Employment and Equity, the University of Newcastle, Working Paper
Keywords: Employment -- Labour Markets; Employment -- Labour mobility; Employment; Labour market; Employment and unemployment